Hispanic children and the obesity epidemic: Exploring the role of abuelas - Pulgarón, Elizabeth R. (2013)
OBJECTIVE: This study evaluated the rate of Hispanic children who have grandparents involved in caretaking and whether grandparents’ involvement has a negative impact on feeding practices, children's physical activity, and body mass index (BMI). METHOD: One hundred and ninety-nine children and their parents were recruited at an elementary school. Parents completed a questionnaire regarding their children's grandparents’ involvement as caretakers and the feeding and physical activity practices of that grandparent when with the child. Children's height and weight were measured and zBMI scores were calculated. RESULTS: Forty-three percent of parents reported that there was a grandparent involved in their child's caretaking. Grandparents served a protective role on zBMI for youth of Hispanic descent, except for the Cuban subgroup. There was no relationship between grandparent involvement and feeding and physical activity behaviors. CONCLUSIONS: In some cases grandparents may serve a protective function for childhood obesity. These results highlight the need for future research on grandparents and children's health, especially among Hispanic subgroups.